Comparative Analysis of Surface Data of Modeled and Observed Winds (Part 1) - Saavedra, Miguel (2018)
In the present work, the realism of the superficial wind simulations carried out with the model is evaluated emph Weather Research and Forecasting (WRF) is evaluated, with data obtained from the QuikSCAT (Quick Scatterometer) satellite. The meridional and zonal speeds of the wind are used as comparison parameters, as well as the stresses produced on the surface of the water. The knowledge of the configuration of the wind on the oceanic surface is important because it generates processes such as the upwelling, the spiral and the Ekman pumping. The intensity with which these processes are carried out determines the diversity and biological and shing richness of a region. The behavior of the wind is analyzed in terms of its horizontal speeds, the effort produced by these speeds, which determine the drag on a free surface and the rotational wind. Correlations greater than 0.6 are obtained in the oceanic areas, far from the coast, while for coastal regions the correlations are less than 0.4.